MANAGEMENT OF EDUCATIONAL FACILITIES AND INFRASTRUCTURE TO IMPROVE THE QUALITY OF LEARNING AND EXTRA ROBOTIC : Case Study at Man 01 Kota Kediri - Ridwanulloh, M. Ubaidillah; Nabila, Zulfa; Afifah, Rizki Amilatul; Jannah, Siti Rodhotul; Putra, Fredi Ganda (Idaarah: Jurnal Manajemen Pendidikan, 2023)
The educational process, of course, requires adequate facilities or infrastructure. If the school has facilitated by providing infrastructure to support learning, then both teachers and students will be able to utilize and optimize the learning process and training activities at school. This study aims to determine the implementation of the utilization of facilities and infrastructure in learning and training in robotic activities at MAN 1 Kediri City. MAN 1 Kota Kediri is one of the madrasahs that organizes superior skills. With the complete facilities and infrastructure in MAN 1 Kota Kediri, it will be easier to improve the quality of academic and non-academic learning. The research method used in this research is descriptive qualitative method. Sources of data taken through interviews, observation, and documentation. One of the superior skills in MAN 1 Kota Kediri is robotics. This skill is still quite new but is in demand by many students. The results of the management of facilities and infrastructure for MAN 01 Kota Kediri run effectively and efficiently. The impact of the management of facilities and infrastructure is that learning programs and extra robotic programs can run well. Several achievements and trophies from the extra robotic program were achieved from competitions that were participated in at both regional and national levels.